EVALUASI ASPEK SOSIO-EMOSIONAL PADA ANAK - MIftahul Munir; M Mansyur (LP2M IAI Miftahul Ulum Pamekasan, 2017)
Socio-emotional development in early childhood is an aspect that needs to be developed and also as a characteristic form of various changes, this will be able to develop various developments that exist in students who are still at an early age stage. So the researchers wanted to know and analyze the evaluation of socio-emotional aspects at the early childhood stage in PAUD Al-Hammadaa, trasak ban on Pamekasan. This research uses qualitative research methods using structured interviews and non-participant observation. While the data analysis used descriptive analysis. From the results of interviews and observations, it was found that the evaluation of the socio-emotional aspects of early childhood at Al-Hammadaa PAUD uses formative and summative evaluation types with its implementation using oral and written techniques. Meanwhile, the factors that influence the socio-emotional of infancy age children at PAUD Al-Hammadaa Trasak Pamekasan are an atmosphere that is not conducive and unpleasant, educational play tools in the classroom and outside the classroom, props, and facilities and infrastructure.